KAJIAN KOMPOSISI PUPUK NPK TERHADAP HASIL BEBERAPA VARIETAS TANAMAN BUNCIS TEGAK (Phaseolus vulgaris L.) DI TANAH ALFISOL - Slamet Minardi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2002)
An experiment concerning the study o/NPK fertilizer composition to the yield of varieties ofbeans (Phaseolus  vulgaris L.) had been carried out in Sukosari,  Jumantono,  Karanganayr. The kind of soil is Alfisol. The experiment was arranged with split plot design basically with randomized Completely Block Design  (RCBD), consist of two factors and three replications. Varieties (V) as main plot,   consist of 3 levels : Strike,  Tendergreen, and  Richgreen, NPK composition treatment (P) as  subplot, consist of 4  levels:   (0:0:0),  (15:10:15),   (15:15:15),  and (10:15:10). The result of the experiment showed that NPK fertilizer composition increases the height of plant; the number of pods per plant, the weight of pods per plant, the dry weight of straw and length of pods. There wasn't an interaction effect of between NPK fertilizer composition and variety of all parameters.